Cross‐reactivity of each fraction among cereals in children with wheat allergy - Takei, Mari; Saito, Akemi; Yanagida, Noriyuki; Sato, Sakura; Ebisawa, Motohiro (Pediatric allergy and immunology, 2022)
Background Cross‐reactivity between wheat and other cereals is a crucial issue in the management of wheat allergy. Few studies have reported in vitro cross‐reactivity in immediate‐type wheat allergy. The aim of this study aimed to examine cross‐reactivity of the three fractions (albumin/globulin, gliadin, and glutenin fractions) among cereals in children with wheat allergy. Methods Sera from 128 children with immediate‐type wheat allergy were collected. Specific immunoglobulin E (sIgE) levels against each fraction of wheat, barley, and rye were measured by enzyme‐linked immunosorbent assay (ELISA). Cross‐reactivities of each fraction among wheat, barley, and rye were examined via inhibition ELISA. Results All subjects were sensitized to all fractions of wheat, barley, and rye. The wheat sIgE levels were significantly higher than those of barley and rye in all the fractions (p ≤ .001) and were significantly correlated with sIgE levels in each fraction (r = .887–.969, p < .001). Inhibition ELISA revealed that wheat inhibited the IgE binding to most of the solid phases at lower protein levels compared with barley and rye in all fractions. Conclusions In children with immediate‐type wheat allergy, sensitization to all the three fractions of wheat was observed. In addition, they showed sensitization to barley and rye caused by in vitro cross‐reactivity with wheat in each fraction. When managing children with wheat allergy, sensitization to barley and rye caused by the cross‐reactivities should be considered.